2020
DOI: 10.3390/w12113273
|View full text |Cite
|
Sign up to set email alerts
|

Floating Wetland Islands Implementation and Biodiversity Assessment in a Port Marina

Abstract: Floating wetland islands (FWI) are considered nature-based solutions with great potential to promote several ecosystem services, such as biodiversity and water quality enhancement through phytoremediation processes. To our knowledge, the present work is the first to scientifically document the in-situ establishment of an FWI in a seawater port marina. The establishment and performance of a cork floating platform with a polyculture (Sarcocornia perennis, Juncus maritimus, Phragmites australis, Halimione portula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
10
0
1
Order By: Relevance
“…However, floating islands could never realistically be that large due to the negative shading effect on submerged vegetation. More than their impact on nutrient regulation, the stakeholders appreciated their potential role as biodiversity hotspots and a habitat for birds, insects, and aquatic fauna [51,52]. Those aspects seem more promising than their use purely for nutrient removal in eutrophicated waters, where the size limits the efficiency.…”
Section: Expert-and Stakeholder-based Esa Approachmentioning
confidence: 99%
“…However, floating islands could never realistically be that large due to the negative shading effect on submerged vegetation. More than their impact on nutrient regulation, the stakeholders appreciated their potential role as biodiversity hotspots and a habitat for birds, insects, and aquatic fauna [51,52]. Those aspects seem more promising than their use purely for nutrient removal in eutrophicated waters, where the size limits the efficiency.…”
Section: Expert-and Stakeholder-based Esa Approachmentioning
confidence: 99%
“…The FTW are considered a valuable phytoremediation tool and a nature-based solution that delivers a range of ecosystem services, such as biodiversity promotion and water quality enhancement, among others. They can be applied in different contexts dealing with fresh and saline water, and wastewater [42][43][44].…”
Section: Relevance Of Ftw For Water Quality Managementmentioning
confidence: 99%
“…For example, the plants used in DC are halophytes, typically from saline and brackish environments, and have also been applied in FTW in port marina environment, although the establishment of H. portucaloides was not so successful as Sarcocornia spp. [42]. Another application of S. fruticosa, with phytoremediation purposes, was considered for highly saline wastewater treatment with constructed wetlands, where it has shown high resilience [46].…”
Section: Relevance Of Ftw For Water Quality Managementmentioning
confidence: 99%
“…Currently, they are being used to treat hypertrophication, sewage and domestic wastewater, combined sewer overflow, contaminated groundwater, stormwater, acid mine drainage, poultry effluent, piggery effluent, boron-enriched water, polluted river water, and nutrients-enriched water [7]. However, the FWs technology in coastal and marine environments has been mainly used for erosion control, food web support, aesthetic improvement, and sediment trapping, but solid scientific documentation of these applications is limited [5,9]. Especially concerning the treatment of hydrocarbons and other marine contaminants with floating wetlands, a gap in scientific research and knowledge has been identified, and even the treatment of these contaminants with conventional constructed wetlands has been sparse [5,9,10], but with increasing research interest in recent years [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the FWs technology in coastal and marine environments has been mainly used for erosion control, food web support, aesthetic improvement, and sediment trapping, but solid scientific documentation of these applications is limited [5,9]. Especially concerning the treatment of hydrocarbons and other marine contaminants with floating wetlands, a gap in scientific research and knowledge has been identified, and even the treatment of these contaminants with conventional constructed wetlands has been sparse [5,9,10], but with increasing research interest in recent years [11].…”
Section: Introductionmentioning
confidence: 99%